Analisis Faktor-Faktor Yang Mempengaruhi Volume Pembiayaan Berbasis Bagi Hasil Pada Bank Umum Syariah Di Indonesia Periode 2011-2015 - Puspitosari, Ping Ping, Dr. Erma Setiawati, MM, Ak, CA (2017)
Islamic banking is a financial institution that serves as an intermediary between the parties that have surplus funds and those who need funds. As intermediary institution, Islamic bank perform its role by channeling funds for financing. There are several products of financing that provided by Islamic bank, one of them is profit and loss sharing based of financing. The attempt of Islamic bank in channeling its funds for financing was not apart from the risks, therefore good management and control are needed. Islamic bank should observe the factors that may affect on financing. The purpose of this study was to analyze the factors that influence profit and loss sharing based of financing of islamic bank. The sample use in study is the Quartely Financial Statement Islamic Commercial Banks in Indonesia period of 2011-2015. The samples used are selected using purposive sampling technique and there are 5 banks that meet the criteria. The data used in this study are secondary data that obtained from published financial statement and downloaded through the official website of Commercial Banks in Indonesia. The method of data analysis used in this study is multiple linear regression analysis with significant level of 5%. From the result of the analysis show that DPK has positive significant influence to financing, while NPF, FDR, ROA and CAR have no influence to financing. Stimulatingly teh DPK, NPF, FDR, ROA and CAR have significances influence to financing it proved sig-F value 0,000 lower than 5% significances. Predictable of the five variables toward financing is 90,7 % as indicated by adjusted R2 while the rest 9,3% is affected by other factors is not include into yhe research model. Keyword: Financing based on profit and loss sharing, Third Party Funds (DPK), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Return on Asset (ROA), Capital Adequacy Ratio (CAR).